On Variation of Product Cordial Labeling of Subdivision of Flower and Its Path Union - Philomena, Sharon V; Priyadharshini, T (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we prove that the subdivision of Flower graph and the Path union of copies of subdivision of Flower graphs are Product cordial graph and Total product cordial graphs. We also extend to prove that the path union from the outer vertex of the subdivision of Flower admits Product cordial and total product cordial labeling